Influence of magma intrusion and contact distance onthermal effects of low-temperature oxidation processes in coal - Zhijin YU; Ce JIN; Xu TANG; Zhipeng ZHANG; Hu WEN (Meitan xuebao)
Magma intrusion into coal seams is widely existed in China, and the structure and components of the coal body are changed after intrusion to form a high-order metamorphic coal, but its spontaneous combustion characteristics are not clear. It is a great significance to explore the effect of magma intrusion on the low-temperature oxidization characteristics of coal, and to prevent and control spontaneous combustion disasters in mining magma-eroded coal seams. Taking the −350 working face in the second mining area of the Xin'an Coal Mine as the engineering background, the coal samples were collected at different distances from the magma intrusion on the spot. By testing the industrial composition and analyzing the differences in the surface morphology of the samples, it was concluded that magma intrusion metamorphosed the raw coal and increased the number of pores and fissures on the surface, mainly through contact thermal evolution. The metamorphic coals were categorized into strongly eroded coals, weakly eroded coals, and high rank coals of the homogeneous group. Based on fixed carbon, ash, specular group reflectance, and paleo temperature, the distribution range of different intrusive metamorphic coals was calculated by curve backpropagation, and the influence range of magmatic intrusion was predicted to be about 172.34%−234.68% of the width of the intrusive body. A comparative study of the oxidative thermal effect of magma intrusion on metamorphic coal and raw coal was carried out by using C80 microcalorimeter. And the results showed that under different air supply conditions, compared with the original coal, the initial exothermic and thermal equilibrium temperature points in the low-temperature oxidation stage were advanced by 0.2−3.4 ℃ and 1.9−18.2 ℃ for strongly eroded, weakly eroded, and homogeneous high-order coals, the total exothermic capacity was increased by 1.72%−135.75%, and the apparent activation energy was reduced by 1.62%−69.02%, and the closer the metamorphic coal was to the magma intrusion, the more oxidizing and exothermic it was, and the shorter the natural ignition period was. Under the condition of sufficient oxygen supply, magma intrusion enhanced the exothermic capacity of oxidation reaction of the strongly eroded coal within the range of 1.01−2.68 m from the magma intrusion, and its mining volume only accounted for about 6.23%−12.15% of the influence range of the magma intrusion. Therefore, when mining back into the magma intrusion area, the prevention and control of spontaneous combustion of strongly eroded coal should be strengthened, and the critical value of the coal spontaneous combustion forecast index in this area should be corrected in time, so as to guarantee the safe mining of coal seams.